Functionalizing Gold Nanoparticles with Calix[4]arenes Monolayers for Enhancing Selectivity and Stability in ORR Electrocatalysis. Issue 23 (12th November 2020) - Lenne, Quentin; Mattiuzzi, Alice; Jabin, Ivan; Le Poul, Nicolas; Leroux, Yann R.; Lagrost, Corinne
Abstract: The deliberate surface modification of nanocatalysts with organic ligands has recently emerged as a promising strategy to boost their efficiency, durability, and/or selectivity in key electrocatalytic processes. The interface between the metallic interface and the immobilized ligands promotes high electrocatalytic activity. Herein, the oxygen reduction reaction activity of gold nanoparticles functionalized with a covalently bound monolayer of calix[4]arenes is compared with commercially available gold nanoparticles, classically stabilized through electrostatic adsorption of citrates onto the gold surfaces. Nanocatalysts coated by calix[4]arenes show enhanced selectivity and stability compared to their citrate‐stabilized counterparts. These nanohybrids exhibit excellent activity with a dominant 4‐electron reduction of O2 with good electrocatalytic performances along with a high robustness under operation as revealed by X‐ray photoelectron spectroscopy analyses. Abstract : Designing gold‐calix[4]arene nanohybrids for enhancing selectivity and stability in oxygen reduction reaction.